The mediating role of the 5Cs of PYD in the relationship between grit and academic adjustment in Spanish undergraduates - Diego Gomez-Baya; Ana Kozina; Jet Uy Buenconsejo; José Antonio Muñiz-Velázquez (Frontiers in Education)
IntroductionAcademic success paves the way for positive youth (and adult) development, leading to short- and long-term positive outcomes. In the case of Spain, research has identified the need to pay closer attention to youth academic performance and well-being. Grit is one of the more consistent predictors of academic adjustment, with possible mediators not yet explored.MethodsThe present study aimed to analyze the mediational role of the 5Cs (i.e., Competence, Confidence, Connection, Caring, and Character) of Positive Youth Development (PYD) on the relationship between the dimensions of grit (i.e., perseverance of effort and consistency of interest) and different academic adjustment indicators (i.e., perceived academic performance, academic stress, and academic boredom), in a sample of Spanish undergraduates (N = 370, 67.2% women, Mage = 21.29, SDage = 3.61) using a cross-sectional study design.ResultsPerseverance of effort was associated with higher perceived academic performance and less academic stress, whereas consistency of interest was associated with lower academic boredom. These associations were partially mediated by specific Cs of PYD. Confidence, Competence, and Connection were related to better academic performance, less academic stress, and less academic boredom. Caring had a controversial positive effect on academic stress.DiscussionThese results have implications for practice in the university context, indicating the need to integrate grit (both dimensions) and PYD promotion interventions, as they could have a synergetic effect to foster academic and vocational success in undergraduate samples.